212k views
4 votes
Bonus Question

Solve 2a-b+c= -5

a - b+c= -5 by subsittution

2a + b =5


A. a= -2,b=0,c = -2


B. a= -2,b=0,c = -1


C. a= 1,b = 3,c= -6


D. a= 1,b = 3,c = -4

User Ries
by
5.9k points

1 Answer

2 votes

Answer:

Please find the answer below

Explanation:

2a-b+c= -5 ----(A)

a-b+c= -5 ------(B)

2a+b =5 -------(C)

from equation A subtracting 2a from both sides we get

-b+c = -5-2a

Substituting this value in B

a-5-2a=-5

a-2a-5+5=0

-a=0

a=0

Putting this value in C

2(0)+b=5

b=5

Putting these values in B

0-5+c=-5

c=0

We do not have any option with these solutions . Hence, it seems that there is something missing from the equation.

User Shayan Ghosh
by
6.0k points